1995
DOI: 10.1103/physrevb.52.4050
|View full text |Cite
|
Sign up to set email alerts
|

Defect structure in neutron-irradiated β6LiAl and β7LiAl: Ele

Abstract: The neutron-irradiation effects on the electrical resistivities of p-LiA1 and p-LiA1 with 48 -54 at. % Li at room temperature are presented. A remarkable decrease of the electrical resistivity is observed in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…V Li is the dominant defect for the Li-deficient region, Li Ga is the dominant defect for the Li-rich one. The coexistence V Li of Li Ga is expected to form V Li -Li Ga complex defects [10] as reported for the defect structure of -LiAl [9], which would play an important role in reducing the strain energy caused by the point defects in the real cystal. Especially, almost the same amounts of V Li and Li Ga exist around the content of 51 at.% Li.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…V Li is the dominant defect for the Li-deficient region, Li Ga is the dominant defect for the Li-rich one. The coexistence V Li of Li Ga is expected to form V Li -Li Ga complex defects [10] as reported for the defect structure of -LiAl [9], which would play an important role in reducing the strain energy caused by the point defects in the real cystal. Especially, almost the same amounts of V Li and Li Ga exist around the content of 51 at.% Li.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the concentration of the radiation-induced defects like a frenkel pair is several order of magnitude smaller than that of the native defects and the effects of the radiation-induced defects are negligibly small [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of Li was determined by the electrical resistivity measurements, relying on the systematic correlation between them (Kuriyama et al, 1996) as shown in Fig. 7 (Kuriyama et al, 1996) as reported for the defect structure of β-LiAl (Sugai et al, 1995), which would play an important role in reducing the strain energy caused by the point www.intechopen.com defects in the lattice matrix. Especially, almost the same amounts of V Li and Li Ga exist for the composition of about 51 at.…”
Section: Methodsmentioning
confidence: 99%
“…% Li for LiIn). In order to understand the motion of Li in the β phase as an ionic conductor, the defect structure in the Li compounds, closely related to the fast ionic motion, has been intensively studied via the measurement of electrical resistivity and density with help of the standard x-ray diffraction analysis (Sugai et al, 1995;Kuriyama et al, 1996). There exist three kinds of defects (see Fig.…”
Section: An Application For Measuring Diffusion Coefficients In LI Iomentioning
confidence: 99%